Implementación de una máquina prototipo para la separación y remoción de partículas ferromagnéticas de neumáticos triturados. - Martínez Moreira, Jhon Alexis (2020)
This research project is based on an implementation of a prototype machine for the separation and removal of ferromagnetic particles from crushed tires, using scientific references as a bibliographic background on the separation and removal of ferromagnetic particles in tire crushing processes, developed in favor of students of the Engineering Major in Electromechanics of the Universidad Técnica de Cotopaxi Extensión La Maná, for the construction of the prototype machine, it was modeled using Autodesk Inventor software which complies with the parameters of modeling and analysis of the elements, using the Von Mises method and finite elements applied to the elements of the prototype machine, in the manufacture of the magnetic drum was used 8-inch pipe in AISI 304 steel as an ideal material, since the same properties of this material provide higher quality at work by being low in magnetic conductivity, with the implementation of C8 ceramic magnets generating a magnetic field that facilitated the separation and removal of metallic impurities from the product such as crushed NFU rubber, the final product of the process is used in the manufacture of synthetic floors, waterproofing and even metal particles will have their final destination to the large metallurgical industries, the project achieved a high social impact since it is an alternative of job creation creating a social culture, once the prototype was designed, the equipment was assembled to develop the respective tests to ensure proper separation and removal of ferromagnetic particles.